Short-Term Outcomes After COVID-19-Related Treatment Interruption Among Patients with Neovascular Age-Related Macular Degeneration Receiving Intravitreal Bevacizumab - Allegrini D; Raimondi R; Montesano G; Borgia A; Sorrentino T; Tsoutsanis P; Romano MR (Clinical Ophthalmology, 2021)
Davide Allegrini,1 Raffaele Raimondi,2 Giovanni Montesano,3 Alfredo Borgia,2 Tania Sorrentino,2 Panagiotis Tsoutsanis,2 Mario R Romano1,2 1Eye Center, Humanitas, Bergamo, Italy; 2Department of Biomedical Sciences, Humanitas University, Milano, Italy; 3University of London - Optometry and Visual Sciences, London, UKCorrespondence: Raffaele RaimondiDepartment of Biomedical Sciences, Humanitas University, Via Rita Levi Montalcini 4, Pieve Emanuele, Milano, ItalyTel +39 02 8224 7100Email raffor9@gmail.comPurpose: To assess outcomes and recovery strategy of patients undergoing intravitreal injections for exudative age-related macular degeneration who experienced COVID-19 related interruption in treatment during complete lockdown.Methods: This was a retrospective, observational case study. We used a mixed effect model with random intercepts to evaluate best corrected visual acuity (BCVA) accounting for measured central macular thickness (CMT) and individual variability of each eye. Furthermore, we analysed measures of the pigmented epithelium detachment as well as presence of subretinal fluid and intraretinal cysts.Results: We included 39 patients and we found a significant reduction in the BCVA between the pre- and post-lockdown controlling for CMT. There was no significant difference in pigmented epithelium detachment and in presence of subretinal fluid and intraretinal cysts.Conclusion: We detected a significant loss in visual function. The magnitude of the average loss was, however, limited suggesting good efficacy of the recovery strategy.Keywords: IVT interruption, covid-19, intravitreal injection, bevacizumab